Svolgere senza X SOSTITUZIONE.
Svolgere senza X SOSTITUZIONE.
$\int_0^1 (\frac{x-1}{\sqrt{4-x^2}} \, dx =$
$\int_0^1 (\frac{x}{\sqrt{4-x^2}} \, dx - \int_0^1 (\frac{1}{\sqrt{4-x^2}} \, dx =$
$= \left. -\sqrt{4-x^2} - arcsin(\frac{x}{2}) \right|_0^1 =$
$ = -\sqrt{3} - \frac{\pi}{6} + 2 $
Sviluppiamo a parte i due integrali
1°.
$ \int \frac{x}{\sqrt{4-x^2}} \, dx = $
$ = -\frac{1}{2}\int (4-x^2)^{-\frac{1}{2}} \; (-2x) \, dx = $
$ = -\frac{1}{2} \cdot 2 (4-x^2)^{\frac{1}{2}} + c = $
$ = - \sqrt{4-x^2} + c $
2°.
$ = \int \frac{1}{\sqrt{4-x^2}} \, dx = $
$ = \frac{1}{2} \int \frac{1}{\sqrt{1-(\frac{x}{2})^2}} \, dx = $
$ = \frac{1}{2} \cdot 2 arcsin(\frac{x}{2})^2 + c = $
$ = arcsin(\frac{x}{2}) + c $